Pengembangan Media Pembelajaran Berbasis Gamifikasi pada Materi Sejarah Kebudayaan Islam Kelas 10 SMA - Rizki Fauzan; Sayyid Arkan Nizami; Fajar Trihadi; Aghil Syarif; Aaliyah Putri; Ahmad Nur Fahmi (Yayasan Al-Afif, 2025)
The development of gamification-based learning media in Islamic Cultural History materials is motivated by several problems encountered in the learning process, such as students’ low learning motivation and the use of instructional media that still tends to be conventional. This condition indicates the need for innovative learning media that encourage active student participation while creating an enjoyable learning experience, particularly in the topic of Walisongo da’wah. This study aims to develop gamification-based learning media that are valid and feasible for use in the learning process. This development research employed the Research and Development (R&D) method using the 4D Thiagarajan model, which consists of four main stages: define, design, develop, and disseminate. However, this study was limited to the develop stage and did not proceed to the disseminate stage. The development stage was conducted through validation by material experts and media experts, followed by product revisions based on the experts’ suggestions and feedback. Data collection techniques included field observations and interviews for needs analysis, as well as validation questionnaires based on a Likert scale, which were analyzed by calculating the percentage of media feasibility. The results of the development indicate that the gamification-based learning media developed fall into the valid category according to expert assessments, with several notes for improvement. After revisions were made in accordance with expert suggestions, the developed learning media were declared feasible for use in Islamic Cultural History learning.Gamification, Islamic Cultural History, Learning Media, R&D.